1986
DOI: 10.1128/mcb.6.2.530-538.1986
|View full text |Cite
|
Sign up to set email alerts
|

Single Base-Pair Mutations in Centromere Element III Cause Aberrant Chromosome Segregation in Saccharomyces cerevisiae

Abstract: In this paper we show that a 211-base pair segment of CEN3 DNA is sufficient to confer wild-type centromere function in the yeast Saccharomyces cerevisiae. We used site-directed mutagenesis of the 211-base pair fragment to examine the sequence-specific functional requirements of a conserved 11-base pair segment of centromere DNA, element III (5'-TGATTTATCCGAA-3'). Element III is the most highly conserved of the centromeric DNA sequences, differing by only a single adenine X thymine base pair among the four cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
3
7
0
Order By: Relevance
“…Figure 1E, F) with a photobleaching step distribution similar to other previously characterized dimeric proteins [59, 60]. This is consistent with structural studies that show that Ndc10 is a homodimer within the CBF3 complex [31, 55, 57, 61] and with the range reported in vivo [48]. Photobleaching analysis of Cse4 CENP-A associated with CEN3 DNA yielded similar results, with the majority of Cse4 CENP-A -GFP photobleaching in two steps (Supp.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Figure 1E, F) with a photobleaching step distribution similar to other previously characterized dimeric proteins [59, 60]. This is consistent with structural studies that show that Ndc10 is a homodimer within the CBF3 complex [31, 55, 57, 61] and with the range reported in vivo [48]. Photobleaching analysis of Cse4 CENP-A associated with CEN3 DNA yielded similar results, with the majority of Cse4 CENP-A -GFP photobleaching in two steps (Supp.…”
Section: Resultssupporting
confidence: 89%
“…While we aim to further investigate this mechanism, either possibility yields a model of Scm3 HJURP -catalyzed Cse4 CENP-A nucleosome formation that is supported by in vitro reconstitutions, where it was found that Scm3 HJURP was required to form a Cse4 CENP-A nucleosome on the highly AT-rich (and thus inherently unfavorably for histone wrapping) centromeric DNA [30]. In addition, this is consistent with in vivo studies that showed Scm3 HJURP coordinates with Ndc10 to deposit Cse4 CENP-A at the centromere and is persistent at centromeres after Cse4 CENP-A deposition, although undergoing rapid exchange [30,55].…”
Section: Formation Of a Native Centromeric Nucleosomesupporting
confidence: 69%
See 1 more Smart Citation
“…The two short CDEI and CDEIII motifs are highly conserved, and function to bind CBF1 and CBF3 respectively, two protein complexes that are specific to the point centromere-kinetochores of budding yeast (Baker and Masison, 1990; Cai and Davis, 1990; Lechner and Carbon, 1991; Mellor et al, 1990). Whereas CDEIII and CBF3 are essential for viability (Doheny et al, 1993; Goh and Kilmartin, 1993; Hegemann et al, 1988; Jehn et al, 1991; Lechner and Carbon, 1991; McGrew et al, 1986; Ng and Carbon, 1987; Panzeri et al, 1985), cells with CDEI disrupted remain viable but exhibit mitotic chromosome loss, and defective centromere function in meiosis I (Cumberledge and Carbon, 1987; Gaudet and Fitzgerald-Hayes, 1989; Hegemann et al, 1988; Niedenthal et al, 1991; Panzeri et al, 1985). CDEII is less well conserved, however, its AT-rich DNA sequence is proposed to be favorable for CENP-A Nuc wrapping due to its increased tendency to curve (Bechert et al, 1999; Koo et al, 1986; Murphy et al, 1991; Ortiz et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…We believe that these sequences, once identified, will prove to be elements that control the choice between reductional or equational segregation not only in "mixed meiotic segregation'' but in regular meiosis as well. Studies of meiotic segregation in strains with mutated centromeres (PANZERI et al 1985;MCGREW, DIEHL and FITZGERALD-HAYES 1986;CUMBERLEDCE and CAR-1989) indicate that the subcentromeric element CDEIII is important for mitotic segregation, whereas CDEI and CDEII are important for the first meiotic segregation. These latter elements are possible candidates for the chromosomal structures which make the segregation choice in "mixed" meiosis.…”
Section: Discussionmentioning
confidence: 99%